"To use or not to use" understanding mountaineers' smartphone use in high-alpine environments. (7th August 2020) - Warner, Robert P.; Adanin, Kristina; Szolosi, Andrew
Abstract: As smartphone use continues to become more embedded within daily life, identifying the factors driving their use in extreme environments may have numerous meaningful implications. Little is currently known about mountaineers' intentions to use smartphones in high-alpine environments. Therefore, the purpose of this study was to examine the extent to which attitude, subjective norm, and perceived behavioral control predicted mountaineers' intentions to use smartphones in high-alpine environments. A sample of 167 mountaineers from 37 countries completed a brief questionnaire about their intentions to use smartphones during their next high-alpine expedition. A series of multiple regression analyses were used to determine the salient beliefs influencing mountaineers' smartphone use in high-alpine environments. The study findings provide a better understanding of the potential factors driving mountaineers' use of smartphones. More broadly, these findings add to the growing body of literature regarding smartphone use in extreme environments.